2017
DOI: 10.1007/s40879-017-0201-1
|View full text |Cite
|
Sign up to set email alerts
|

Rationally connected non-Fano type varieties

Abstract: Varieties of Fano type are very well behaved with respect to the MMP, and they are known to be rationally connected. We study a relation between the classes of rationally connected varieties and varieties of Fano type. It is known that these classes are birationally equivalent in dimension 2. We give examples of rationally connected varieties of dimension 3 which are not birational to varieties of Fano type, thereby answering the question of Cascini and Gongyo [2, Question 5.2].

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…There are analogs of these results for surfaces over non-closed fields. Similar question for del Pezzo fibrations was studied by I. Krylov [Kry18]. 14.6.…”
Section: Theorem ([Kol17]supporting
confidence: 54%
“…There are analogs of these results for surfaces over non-closed fields. Similar question for del Pezzo fibrations was studied by I. Krylov [Kry18]. 14.6.…”
Section: Theorem ([Kol17]supporting
confidence: 54%
“…Theorem 0.1. Assume that dim F 4 and every fibre F of the projection π is a variety with at most quadratic singularities of rank at least 4, and moreover codim(Sing F ⊂ F ) 4. Assume further that every fibre F satisfies the conditions (h), (hd) and (v), whereas the fibre space V /S satisfies the K-condition K 2condition.…”
mentioning
confidence: 99%
“…Finally, let us point out the recent work [4], where by means of the results of [6,7] (see also [8,Chapter 7]) the problem of existence of rationally connected varieties that are non-Fano type varieties, stated in [3], was solved.…”
mentioning
confidence: 99%
“…However, the converse is not true (the blow-up of P 2 in 10 very general points provides an obvious counterexample). In the recent paper [Kry15] it is shown that there exist smooth rationally connected varieties of dimension n ≥ 4 that are not birationally equivalent to a variety of Fano type.…”
Section: Introductionmentioning
confidence: 99%
“…Krylov then asked the following question. Question 1.1 (see [11,Remark 5.7]). Let X be a rationally connected variety.…”
Section: Introductionmentioning
confidence: 99%